A Classic Dermatomyositis: A Case Report of Rare Idiopathic Inflammatory Myopathy - Satyawardhana; Awalia (Gaceta Médica de Caracas, 2023)
Background: Dermatomyositis (DM) is a rare autoimmune disease and is one of the idiopathic inflammatory myopathies which predominately affects the skin and muscles. Its estimated incidence is less than 10 cases per million population with an overall female/male ratio is approximately 2:1. This case report presents a classic case of dermatomyositis in a male in Indonesia.